UTERINE BLEEDING IN PUBERTY — PRINCIPLES OF INTERDISCIPLINARY SOLUTION - E.V. Uvarova; N.M. Veselova; I.A. Sal'nikova; I.M. Lobodina (Вопросы современной педиатрии, 2007)
International conventional views on a problem of pubertal uterine bleeding are elucidated in the article. Clinical peculiarities and risk factors, diagnostic methods and therapy of pubertal uterine bleeding in girls is thought out considering multiple factors of pathogenesis and concomitant diseases. Revealed principles of interdisciplinary treatment of girls with uterine bleeding by pediatricians and gynecologists for children and adolescents are designed to facilitate early of premorbid health status, features of reproductive organs development and genital organs state. These steps would allow to hamper pathology progression and result in better levels of reproductive health in mothers in the future.Key words: uterine bleedings in puberty, adolescent girls, gynecology diseases, duagnostics and treatment.